The Influence of Leverage, Profitability and Earnings Power on Earnings Management with Managerial Ownership as a Moderating Variable: Study on Companies Listed on the Jakarta Islamic Index (JII) for the period 2018 - 2022 - Fadlila, Nadiya; Muthohar, Ahmad Mifdlol (Yayasan Meira Visi Persada, 2024)
The purpose of this research is to test and obtain empirical evidence on the influence of leverage, profitability, and earning power on earnings management with managerial ownership as a moderating variable, based on 16 companies listed in the Jakarta Islamic Index from 2018 to 2022. This study employs panel data regression analysis and moderated regression analysis to examine the influence of moderating variables. Data analysis results indicate that leverage does not have a significant positive effect on earnings management. However, profitability and earnings power exhibit a significant positive impact on earnings management. Managerial ownership significantly moderates the influence of earnings power on earnings management. Managerial ownership does not significantly moderate leverage and profitability concerning earnings management. The novelty of this research lies in the addition of the independent variable, earnings power, and the use of managerial ownership as a moderating variable.